Perancangan Interior Restoran Tradisional Jawa Timur Di Surabaya - Susanto, Rizky Alim (Intra, 2015)
Interior Design Traditional Restaurant in Surabaya East Java is the interior design of a restaurant that serves food in addition to the typical East Java also provides an atmosphere there is a traditional East Java. The planned facilities include among others the lobby, dining area table service, self-service dining areas, counter service dining areas, a gazebo, a VIP lounge and restaurant management office. Restaurant service is using the system table service, self-service and counter service, with consideration of the diverse desires of visitors. In accordance with the traditional title of East Java, the design concept of this restaurant raised about custom house joglo of East Java, therefore planned in its design with the application of customary joglo roofs and all the elements - elements that exist in traditional house joglo. That which is intended to strengthen the traditional atmosphere of East Java.